PEO-based elastomer composite solid electrolyte with high room-temperature ionic conductivity and preparation method of PEO-based elastomer composite solid electrolyte
By optimizing the coordination microenvironment between PEO-based elastomer and lithium salt, a PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity was prepared, which solved the problems of low low-temperature ionic conductivity and poor electrode-electrolyte interface stability in the prior art, significantly improving the overall performance of the battery.
Patent Information
- Application Number
- CN202411914826.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
AI Technical Summary
The existing PEO-based composite solid electrolyte has low ion conductivity at room temperature and low temperatures, and poor electrode-electrolyte interface stability, which limits the performance of solid lithium metal batteries.
By optimizing the ratio of PEO to hexamethylene diisocyanate, the ratio of adipic dihydrazide to bis(2-hydroxyethyl) disulfide, the ratio of lithium salt and small molecule plasticizer, and the reaction temperature, the coordination microenvironment between PEO-based elastomer and lithium salt is adjusted to prepare a PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity.
The room temperature ion conductivity, lithium ion transfer number, electrochemical stability and mechanical properties of solid-state lithium metal batteries have been significantly improved, and the overall performance of the battery has been improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a PEO-based elastomer with high room temperature ionic conductivity, in particular to a PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity and a preparation method thereof, belonging to the technical field of electrolyte materials. Background Art
[0002] In recent years, high-energy lithium metal batteries have developed rapidly, but liquid electrolytes are prone to leakage, combustion and other safety issues, which seriously restrict their further development. Using solid electrolytes to replace liquid electrolytes is expected to solve this problem and increase the energy density of batteries. At present, the development of highly safe and scalable solid electrolytes is very urgent.
[0003] The commercialization of solid-state lithium metal batteries is highly dependent on the research and development of solid electrolytes. To this end, scientists at home and abroad have conducted in-depth research and made good progress. Among the many types of solid electrolytes, polymer composite solid electrolytes have the advantages of both polymer electrolytes and inorganic electrolytes, and are the electrolyte system that best meets the commercialization of solid-state lithium metal batteries. Among them, PEO composite solid electrolytes have the advantages of high salt solubility, good compatibility with electrode interfaces, and easy processing, and have great prospects for large-scale practical applications, but they still need to break through the following two technical bottlenecks: The ionic conductivity is low at room temperature and low temperature. The ion transport in the PEO composite solid electrolyte mainly occurs in the amorphous phase and is highly temperature dependent. When the operating temperature is lower than the glass transition temperature of PEO ( T g ), the PEO crystallinity is high, which seriously hinders ion transfer. Therefore, inhibiting PEO crystallization reduces T g , is the key to improving low-temperature ionic conductivity. Specific strategies include PEO chain modification (such as: CN118888839A, CN117096430A), adding plasticizers (such as: Angew. Chem. Int. Ed. 2024,63, e202400091, Adv. Energy Mater. 2023, 13, 2204036, CN202010889688.9, CN201910802415.3), introduction of inorganic nanoparticles (such as: CN202211516554.8, CN202011495087.6, CN202110896051, CN201611225335.9, CN202211302169.3, CN202310009942.5, CN200710144760.X, CN202310047074.X, CN117525574B), etc.
[0004] Poor stability of the electrode-electrolyte interface. During the charge and discharge process of solid-state lithium metal batteries, the positive / negative electrode materials are prone to volume changes, which causes increased stress at the electrode / electrolyte interface, damage to the interface structure, and deterioration of physical contact, ultimately leading to increased battery interface impedance or even failure. Studies have found that highly elastic polymers can provide a conformal contact interface for electrodes that undergo repeated volume changes, thereby ensuring the stability of the electrode / electrolyte interface; by regulating the intramolecular or intermolecular chemical reactions in the polymer network, the mechanical properties of the PEO composite solid electrolyte can be enhanced (Nat. Commun. 2022, 13, 4868, Adv. Mater. 2022, 34, e2205763, J. Am. Chem. Soc. 2022, 144, 17477-17486). For example: Patent CN 112851871 A discloses an elastic solid electrolyte and its preparation method based on the reaction between a rubber material and an ionic liquid; but its room temperature ionic conductivity is still low.
[0005] Based on this, the present invention proposes to optimize the ratio of PEO to hexamethylene diisocyanate, the ratio of adipic acid dihydrazide to bis(2-hydroxyethyl) disulfide, lithium salt and small molecule plasticizer, reaction temperature and other process parameters to effectively adjust the coordination microenvironment between the PEO-based elastomer and the lithium salt, thereby preparing a PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity, solving the key technical bottleneck of low room temperature ionic conductivity of existing solid electrolytes, significantly improving the comprehensive performance of solid-state lithium metal batteries such as capacity, rate performance and cycle stability, and promoting the rapid development of solid-state batteries. Summary of the invention
[0006] The present invention aims to solve the technical problems of low ion conductivity at low temperature and poor stability of electrode-electrolyte interface of existing PEO-based composite solid electrolytes, and provides a PEO-based elastomer composite solid electrolyte with high room temperature ion conductivity and its preparation. + The mutual coordination between them and the regulation of the microenvironment of lithium ion transfer in the solid electrolyte can significantly improve the room temperature ionic conductivity of the composite solid electrolyte.
[0007] 1. Preparation of PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity (1) Synthesis of PEO-based elastomer prepolymer: N, N-Nitrogen is introduced into the dimethylformamide solvent for 10-15 minutes and heated to 75-85 °C. Under this condition, PEO (polyethylene oxide) and hexamethylene diisocyanate are added, and dibutyltin dilaurate catalyst is added, and the reaction is carried out at 75-85 °C for 3-6 hours under nitrogen protection. Wherein, the molar ratio of PEO to hexamethylene diisocyanate is 1:2-1:2.8, and the molecular weight of PEO is 200-80000 g / mol. Process parameters such as raw material ratio and reaction temperature are controlled to ensure the formation of a uniform internal cross-linked network. Subsequently, adipic acid dihydrazide and bis (2-hydroxyethyl) disulfide are added, and the reaction is continued at 75-85 °C for 2-4 hours under nitrogen protection to further regulate the mechanical properties and coordination microenvironment of the PEO-based elastomer; finally, methanol is added to terminate the reaction, and the reaction is continued for 20-40 minutes to obtain a PEO-based elastomer prepolymer. The molar ratio of adipic acid dihydrazide to bis(2-hydroxyethyl) disulfide is 1:0.5-1:5; and the molar ratio of dibutyltin dilaurate catalyst to PEO is 1:20-1:36.
[0008] (2) Preparation of PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity: Take PEO-based elastomer prepolymer, add lithium salt and small molecule plasticizer, stir and treat at 30-80 ℃ in nitrogen atmosphere for 6-48 hours to form a stable emulsion; control process parameters such as raw material ratio and reaction temperature to ensure the formation of a rich lithium ion coordination environment; wait until the temperature drops to room temperature; cool the emulsion to room temperature, cast it into a preheated polytetrafluoroethylene mold, and then vacuum dry it to form a PEO-based elastomer composite solid electrolyte membrane. The key to obtaining high room temperature ionic conductivity of PEO-based elastomer composite solid electrolytes is to optimize the molecular structure of the PEO-based elastomer network, the synergistic effect of small molecule plasticizers, and the precise control of the lithium salt distribution microenvironment.
[0009] The molar ratio of the lithium salt to the small molecule plasticizer is 2.6:1~1:2. The lithium salt is at least one of lithium chloride, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide. The small molecule plasticizer is at least one of succinonitrile and fluoroethylene carbonate. The concentration of the PEO-based elastomer prepolymer is 6~12 mg / mL; the molar volume ratio of the lithium salt to the PEO-based elastomer prepolymer is 0.1~ 0.6 mmol / mL. The vacuum drying is carried out at 55~65°C under vacuum conditions for 10~15 hours.
[0010] The present invention first uses PEO and hexamethylene diisocyanate as monomers and dibutyltin dilaurate as a catalyst, reacts at 75-85°C for 3-6 hours under nitrogen protection to promote the formation of an internal cross-linked network, then adds hydrazine dihydrochloride (ADH) and bis(2-hydroxyethyl) disulfide to further regulate the mechanical properties and coordination microenvironment of the internal cross-linked network, and terminates the reaction by methanol. Then the prepolymer is mixed with lithium salt and small molecule plasticizer in molar ratio, and the reaction conditions are controlled to form a stable emulsion, and the composite solid electrolyte is cast into a film. The PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity prepared by the present invention is different from the elastic solid electrolyte that has been disclosed or reported. The present invention forms a composite solid electrolyte with high ion mobility and a large number of cross-linked lithium ion transfer channels by optimizing the molecular structure of the internal cross-linked network of the PEO-based elastomer network, the synergistic effect of the small molecule plasticizer, and the precise regulation of the lithium salt distribution microenvironment, which has excellent mechanical flexibility and room temperature ion conductivity. The internal cross-linked network molecular structure of the PEO-based elastomer network, the addition ratio of lithium salt and small molecule plasticizer, and the heat treatment conditions directly determine the migration characteristics of lithium ions in the PEO-based elastomer, thereby significantly affecting the ionic conductivity performance of the solid electrolyte.
[0011] 2. Performance of PEO-based elastomer composite solid electrolyte 1. Room temperature lithium ion transfer performance Figure 1 This is a digital photo of the composite solid electrolyte of Example 1. By comparing the ion transfer performance of the solid electrolyte of Comparative Example 1, the following is shown: Figure 2 The experimental results show that the ionic conductivity of the elastic composite solid electrolyte of the present invention can reach 0.36×10 −3 S / cm, the ionic conductivity of the composite solid electrolyte in Comparative Example 1 is only 0.6 × 10 −5 S / cm.
[0012] 2. Lithium ion transfer number The lithium ion transfer numbers of the composite solid electrolyte of Example 1 and the solid electrolyte of Comparative Example 1 are as follows: Figure 3 As shown. The lithium ion transfer number of the composite solid electrolyte in Example 1 is as high as 0.89, which is much higher than the lithium ion transfer number of the solid electrolyte in Comparative Example 1, which is 0.26. 3. Electrochemical stability The electrochemical stability of the composite solid electrolyte of Example 1 and the solid electrolyte of Comparative Example 1 is as follows Figure 4 The electrochemical stability voltage of the composite solid electrolyte in Example 1 is 5.6 V, which is higher than the lithium ion transfer voltage of the solid electrolyte in Comparative Example 1 by 4.8 V.
[0013] 4. Mechanical properties Figure 5The mechanical properties of the composite solid electrolyte invented in Example 1 are characterized. Its tensile strain can reach 956%, and its tensile strength can reach 36 MPa, which shows that the composite solid electrolyte of the present invention has excellent mechanical properties.
[0014] 5. Cycling stability at room temperature The cycle stability of the solid-state lithium metal battery assembled with the composite solid electrolyte of Example 1 and the solid electrolyte of Comparative Example 1 at room temperature is as follows: Figure 6 As shown. The capacity of the solid-state lithium metal battery assembled in Example 1 can reach 127 mAh / g under 1 C conditions, and its capacity retention rate can reach 94.49% after 200 stable cycles. However, the capacity of the lithium metal battery assembled in Comparative Example 1 is only 93 mAh / g after 200 cycles.
[0015] 6. Cycling stability at low temperature The cycle stability of the solid-state lithium metal battery assembled with the composite solid electrolyte of Example 1 and the solid electrolyte of Comparative Example 1 at 0 °C is as follows Figure 7 As shown. The capacity of the solid-state lithium metal battery assembled in Example 1 can reach 119 mAh / g under 1 C conditions, and its capacity retention rate can reach 94.11% after 200 stable cycles. However, the capacity of the lithium metal battery assembled in Comparative Example 1 is only 24 mAh / g after 200 cycles.
[0016] Beneficial effects of the present invention: The present invention successfully prepared a composite solid electrolyte with high ion mobility and excellent room temperature ionic conductivity by optimizing the molecular structure design of the internal cross-linked network of PEO-based elastomers, introducing the synergistic effect of small molecule plasticizers, and accurately regulating the distribution microenvironment of lithium salts. The present invention solves the technical bottlenecks of low room temperature ionic conductivity and poor electrode-electrolyte interface stability of traditional PEO-based composite solid electrolytes, significantly improves the comprehensive performance of solid-state batteries under actual working conditions, and lays a solid material foundation for the research and development of next-generation high energy density and high safety solid-state batteries. Compared with the prior art, the present invention has achieved significant innovations in the following aspects: (1) Molecular structure optimization and network design: By adjusting the ratio of PEO to hexamethylene diisocyanate and introducing the internal cross-linked network of adipic acid dihydrazide and bis(2-hydroxyethyl) disulfide, the present invention significantly enhances the mechanical flexibility and interface stability of the electrolyte, thereby overcoming the problem of brittleness of traditional PEO-based electrolytes under low temperature and high stress conditions. (2) Microenvironmental regulation of lithium salt distribution: By precisely controlling the addition ratio of lithium salt and the synergistic effect with plasticizer, the present invention optimizes the transmission path of lithium ions and forms an efficient ion transfer channel. Compared with the unoptimized PEO-based electrolyte, the room temperature ion conductivity of the composite solid electrolyte designed by the present invention can reach up to 10 −3S / cm, and the lithium ion migration number is as high as 0.9, which is much better than the solid electrolyte in the prior art (<0.5). (3) Excellent comprehensive electrochemical performance: Compared with the traditional system, the composite solid electrolyte of the present invention exhibits excellent electrochemical stability at 5.6 V, expanding the matching with high-voltage positive electrode materials. At room temperature and 0 °C, the assembled solid-state lithium metal battery showed a capacity retention rate of up to 94.49% and 94.11% after 200 cycles, respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Digital photo of a PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity.
[0018] Figure 2 The ionic conductivity of the PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity.
[0019] Figure 3 Lithium ion transfer number of PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity.
[0020] Figure 4 Electrochemical stability of PEO-based elastomer composite solid electrolytes with high room temperature ionic conductivity Figure 5 Mechanical properties of PEO-based elastomer composite solid electrolytes with high room temperature ionic conductivity.
[0021] Figure 6 The cycling stability of solid-state lithium metal batteries assembled with PEO-based elastomer composite solid electrolytes with high room temperature ionic conductivity at room temperature (1 C).
[0022] Figure 7 Cycling stability (1 C) of solid-state lithium metal batteries assembled with PEO-based elastomer composite solid electrolytes with high room temperature ionic conductivity at 0 °C. DETAILED DESCRIPTION
[0023] Example 1 (1) Synthesis of PEO-based elastomer prepolymer: Take 30 mL of N,N-dimethylformamide solvent, nitrogen was introduced for 10 minutes, and heated to 75 ° C, 10 mol PEO (molecular weight 2000 g / mL) and 23 mol hexamethylene diisocyanate were added, the molar ratio of the two was 1:2.3, and dibutyltin dilaurate catalyst (0.5 mol) was added, and the reaction was carried out at 75 ° C for 3 hours under nitrogen protection; then, a mixture of adipic acid dihydrazide (0.2 mol) and bis (2-hydroxyethyl) disulfide (0.3 mol) was added, the molar ratio of the two was 2:3, and the reaction was continued at 75 ° C for 3 hours under nitrogen protection; finally, 0.3 mL methanol was added to terminate the reaction, and the reaction was continued for 30 minutes to obtain a PEO-based elastomer prepolymer.
[0024] (2) Preparation of composite solid electrolyte: Take 10 mL of PEO-based elastomer prepolymer solution (concentration of 8 g / mL), add lithium chloride (0.0028 mol) and fluoroethylene carbonate (0.001 mol) in sequence, with a molar ratio of 2.8:1, and stir at 75 °C for 18 hours under a nitrogen atmosphere to form a stable emulsion; after cooling the emulsion to room temperature, pour it into a preheated polytetrafluoroethylene mold, and then dry it at 60 °C under vacuum for 12 hours to form a PEO-based elastomer composite solid electrolyte membrane.
[0025] Performance: The ionic conductivity of the composite solid electrolyte can reach 0.36×10 −3 S / cm, and the lithium ion transfer number can reach 0.89. Example 2 (1) Synthesis of PEO-based elastomer prepolymer: Take 45 mL of N, N -dimethylformamide solvent, nitrogen was introduced for 10 minutes, and heated to 80 °C, 10 mol PEO (molecular weight 20000 g / mL) and 25 mol hexamethylene diisocyanate were added, the molar ratio of the two was 1:2.5, and dibutyltin dilaurate catalyst (0.33 mol) was added. The reaction was carried out at 80 °C for 5 hours under nitrogen protection; then, a mixture of adipic acid dihydrazide (0.1 mol) and bis(2-hydroxyethyl) disulfide (0.4 mol) was added, the molar ratio of the two was 1:4, and the reaction was continued at 80 °C for 3 hours under nitrogen protection; finally, 0.4 mL methanol was added to terminate the reaction, and the reaction was continued for 30 minutes to obtain a PEO-based elastomer prepolymer.
[0026] (2) Preparation of composite solid electrolyte: Take 20 mL of PEO-based elastomer prepolymer (concentration of 6 g / mL), add lithium chloride (0.004 mol) and succinonitrile (0.03 mol) in sequence, with a molar ratio of 1:1.5. Stir at 60 °C for 24 hours under a nitrogen atmosphere to form a stable emulsion. After the emulsion is cooled to room temperature, it is poured into a preheated polytetrafluoroethylene mold, and then dried at 60 °C under vacuum for 12 hours to form a PEO-based elastomer composite solid electrolyte membrane.
[0027] Performance: The ionic conductivity of the composite solid electrolyte can reach 0.76 × 10 −3 S / cm, and the lithium ion transfer number can reach 0.91.
[0028] Example 3 (1) Synthesis of PEO-based elastomer prepolymer: Take 100 mL of N,N -dimethylformamide solvent, nitrogen was introduced for 10 minutes, and heated to 85 °C; 20 mol PEO (molecular weight 2000 g / mL) and 52 mol hexamethylene diisocyanate were added, the ratio of the two was 1:2.6, and dibutyltin dilaurate catalyst (0.6 mol) was added, and the reaction was carried out at 85 °C for 6 hours under nitrogen protection; then, a mixture of adipic acid dihydrazide (1 mol) and bis(2-hydroxyethyl) disulfide (2 mol) was added, the molar ratio of the two was 1:2, and the reaction was continued at 85 °C for 3 hours under nitrogen protection; finally, 4 mL of methanol was added to terminate the reaction, and the reaction was continued for 30 minutes to obtain a PEO-based elastomer prepolymer.
[0029] (2) Preparation of composite solid electrolyte: Take 100 mL of PEO-based elastomer prepolymer solution (concentration of 10 g / mL), add lithium bis(trifluoromethanesulfonyl)imide (0.05 mol), succinonitrile (0.05 mol), and fluoroethylene carbonate (0.05 mol) in sequence, and stir at 50 °C for 24 hours under a nitrogen atmosphere to form a stable emulsion; after the emulsion is cooled to room temperature, it is poured into a preheated polytetrafluoroethylene mold, and then dried at 60 °C under vacuum conditions for 12 hours to form a PEO-based elastomer composite solid electrolyte membrane.
[0030] Performance: The ionic conductivity of the composite solid electrolyte can reach 0.98 × 10 −3 S / cm, and the lithium ion transfer number can reach 0.87.
[0031] Example 4 (1) Synthesis of PEO-based elastomer prepolymer: Take 200 mL of N,N-dimethylformamide solvent, nitrogen was introduced for 10 minutes, and heated to 75 °C, 40 mol PEO (molecular weight 2000 g / mL) and 88 mol hexamethylene diisocyanate were added, the molar ratio of the two was 1:2.2, and dibutyltin dilaurate catalyst (1.5 mol) was added. The reaction was carried out at 75 °C for 4 hours under nitrogen protection; then, a mixture of adipic acid dihydrazide (4 mol) and bis(2-hydroxyethyl) disulfide (16 mol) was added, the molar ratio of the two was 1:4, and the reaction was continued at 75 °C for 3 hours under nitrogen protection; finally, 8 mL of methanol was added to terminate the reaction, and the reaction was continued for 30 minutes to obtain a PEO-based elastomer prepolymer.
[0032] (2) Preparation of composite solid electrolyte: Take 150 mL of PEO-based elastomer prepolymer solution (concentration of 6 g / mL), add lithium bis(fluorosulfonyl)imide (0.03 mol) and fluoroethylene carbonate (0.1 mol) in sequence, and stir at 80 °C for 12 hours under a nitrogen atmosphere to form a stable emulsion; after cooling the emulsion to room temperature, pour it into a preheated polytetrafluoroethylene mold, and then dry it at 60 °C under vacuum for 12 hours to form a PEO-based elastomer composite solid electrolyte membrane.
[0033] Performance: The ionic conductivity of the composite solid electrolyte can reach 1.1 × 10 −3 S / cm, and the lithium ion transfer number can reach 0.90.
[0034] Comparative Example 1 Take 15 mL of anhydrous acetonitrile, add polyethylene oxide (0.425 g, M = 600000 g / mol), lithium bis(fluorosulfonyl)imide (0.9 mmol), and fluoroethylene carbonate (2.0 mmol) in sequence, and stir at 80 °C for 12 hours under a nitrogen atmosphere to form a stable emulsion; after the emulsion is cooled to room temperature, it is poured into a pre-heated polytetrafluoroethylene mold, and then dried at 60 °C under vacuum conditions for 12 hours to form a composite solid electrolyte membrane.
Claims
1. A method for preparing a PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity, comprising the following steps: (1) Synthesis of PEO-based elastomer prepolymer: N, N -Nitrogen is introduced into the dimethylformamide solvent for 10-15 minutes and heated to 75-85°C. Under this condition, PEO and hexamethylene diisocyanate are added, and dibutyltin dilaurate is added as a catalyst, and the reaction is carried out at 75-85°C for 3-6 hours under nitrogen protection; then adipic acid dihydrazide and bis(2-hydroxyethyl) disulfide are added, and the reaction is continued at 75-85°C for 2-4 hours under nitrogen protection; finally, methanol is added to terminate the reaction, and the reaction is continued for 20-40 minutes to obtain a PEO-based elastomer prepolymer; (2) Preparation of a PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity: Take a PEO-based elastomer prepolymer liquid, add lithium salt and small molecule plasticizer, and stir it at 30-80 °C in a nitrogen atmosphere for 6-48 hours to form a stable emulsion; wait until the temperature drops to room temperature; after the emulsion is cooled to room temperature, it is poured into a preheated polytetrafluoroethylene mold, and then vacuum dried to form a PEO-based elastomer composite solid electrolyte membrane; the molar ratio of the lithium salt to the small molecule plasticizer is 2.6:1~1:
2.
2. The method for preparing the PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity as claimed in claim 1, characterized in that: In step (1), the molar ratio of PEO to hexamethylene diisocyanate is 1:2-1:2.8, wherein the molecular weight of PEO is 200-80000 g / mol.
3. The method for preparing the PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity as claimed in claim 1, characterized in that: In step (1), the molar ratio of the dibutyltin dilaurate catalyst to PEO is 1:20 to 1:
36.
4. The method for preparing the PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity as claimed in claim 1, characterized in that: In step (1), the molar ratio of adipic acid dihydrazide to bis(2-hydroxyethyl) disulfide is 1:0.5 to 1:
5.
5. The method for preparing the PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity as claimed in claim 1, characterized in that: In step (2), the lithium salt is at least one of lithium chloride, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide.
6. The method for preparing a PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity as claimed in claim 1, characterized in that: In step (2), the small molecule plasticizer is at least one of succinonitrile and fluoroethylene carbonate.
7. The method for preparing the PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity as claimed in claim 1, characterized in that: In step (2), the concentration of the PEO-based elastomer prepolymer solution is 6-12 mg / mL; and the molar volume ratio of the lithium salt to the PEO-based elastomer prepolymer solution is 0.1-0.6 mmol / mL.
8. The method for preparing the PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity as claimed in claim 1, characterized in that: In step (2), the vacuum drying is carried out at 55-65° C. under vacuum conditions for 10-15 hours.
9. A PEO-based elastomer composite solid electrolyte with high room temperature ionic conductivity prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
All solid state electrolyte and preparing method and application of the same
CN101183727A
A polymer solid electrolyte material and its preparation method
CN107069081B
Method for preparing modified butanedinitrile-modified all-solid lithium battery
CN110504491A
Solid electrolyte with self-supporting structure, preparation method and application
CN111900460A
Composite solid electrolyte material and preparation method thereof, preparation method of composite solid electrolyte membrane and solid-state battery
CN112563567A
Cited By
Solid polymer electrolyte, preparation method thereof, battery and electric device
CN121726521A